PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR MATEMATIKA SISWA PADA POKOK BAHASAN LINGKARAN DIKELAS VIII MTS.N 2 PADANGSIDIMPUAN - Nursawalina Harahap; Zulhimma Zulhimma; Suparni Suparni (IAIN PADANGSIDIMPUAN, 2017)
This research is basedon students’ less in training so that they difficulty in finishing question on “ circle” topic then they are less active in teaching learning process so that giving impact into student’ mathematics outcomes. This research uses experimental method with untreated control group design with pretest and posttest. The population of this research are all the students at VIII class MTs.N 2 Padangsidimpuan which amounts to 143 students, while the sample of this research is VIII-2 as an experimental class for about 29 students’and VIII-3 as control class for about 28 students. The instrument that is used in this research is essay test that consist of 8 questions about “circle” materials. The result of data analysis in requirement test is obtained by both sample class is normal and homogeneous distribution. The result of t-test are obtained t count =2,065t table = 1.67, resulting in a rejection of O and acceptance Ha. This study concludes that there is a significant effect in using contextual teaching and learning approach to the student’ mathematics learninf outcomes on the “circle” materials at VIII grade MTs. N 2 Padangsidimpuan.